The Hartwick rule: Myths and facts - Geir B. Asheim; Wolfgang Buchholz (University of Oslo, Department of Economics, 2000)
We consider the Hartwick rule for capital accumulation and resource depletion, provide semantic clarifications and investigate whether this rule indicates sustainability and requires substitutability between manmade and natural capital. In addition to shedding light on the meaning of the Hartwick rule by reviewing established results, we establish the following novel finding: The value of net investments being negative does not imply that utility is unsustainable. Throughout we make the assumption of a constant technology, without which the Hartwick rule does not apply.
Keywords: D9; Q01; Q3; 330; Hartwick rule; natural resources; sustainability; Erschöpfbare Ressourcen; Ressourcenökonomik; Intertemporale Allokation; Investition; Nachhaltige Entwicklung; Theorie